2017
DOI: 10.5603/kp.a2016.0155
|View full text |Cite
|
Sign up to set email alerts
|

Both iron excess and iron depletion impair viability of rat H9C2 cardiomyocytes and L6G8C5 myocytes

Abstract: A b s t r a c tBackground: Iron is presumed to play an important role in the functioning of cardiomyocytes and skeletal myocytes. There is scarcity of direct data characterising the cells functioning when exposed to iron depletion or iron overload in a cellular environment. There is some clinical evidence demonstrating that iron deficiency has serious negative prognostic consequences in heart failure (HF) patients and its correction brought clinical benefit. Aim:The viability of the cells upon unfavourable iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…There is also a scarcity of data on the influence of both iron excess and iron deficiency on atrophy markers in skeletal myocytes when exposed to hypoxia. The present authors previously studied the influence of increased or reduced iron availability in hypoxic conditions on skeletal myocytes and demonstrated that, during hypoxia, the reduced iron concentration had a more negative impact on the viability and apoptotic activity of the studied cells as compared with elevated iron availability ( 24 , 42 ). The present authors' preliminary results also demonstrated that, in skeletal myocytes, the mRNA expression of muscle-specific atrophy marker Atrogin-1 was increased upon reduced iron availability, and was downregulated in increased iron concentrations ( 24 ).…”
Section: Discussionmentioning
confidence: 82%
“…There is also a scarcity of data on the influence of both iron excess and iron deficiency on atrophy markers in skeletal myocytes when exposed to hypoxia. The present authors previously studied the influence of increased or reduced iron availability in hypoxic conditions on skeletal myocytes and demonstrated that, during hypoxia, the reduced iron concentration had a more negative impact on the viability and apoptotic activity of the studied cells as compared with elevated iron availability ( 24 , 42 ). The present authors' preliminary results also demonstrated that, in skeletal myocytes, the mRNA expression of muscle-specific atrophy marker Atrogin-1 was increased upon reduced iron availability, and was downregulated in increased iron concentrations ( 24 ).…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, supplementation of transferrin-bound iron reversed all functional and morphological abnormalities. Additionally, our recent research showed that intracellular iron depletion is detrimental for functioning of cardiomyocytes and skeletal myocytes and leads to increased apoptosis and reduces cell viability [57, 58].…”
Section: Iron Homeostasis and Deficiency In The Failing Human Heartmentioning
confidence: 99%
“…Furthermore, treatment by antioxidant could abrogate iron loading-induced muscle atrophy by activating the Akt-FOXO3a pathway [ 105 ]. In vitro, Kasztura et al [ 106 ] used ferric ammonium citrate (FAC) to treat rat skeletal myocyte L6G8C5 cells, which showed reduced myoglobin levels and decreased proliferative activity in an iron overload condition. In hemodialysis patients, increased serum ferritin significantly correlated with handgrip strength and muscle quality, and thus suggested that iron overload should be concerned, to avoid its possibly detrimental effect on muscle in such patients [ 107 ].…”
Section: Iron and Ros Signaling In Spaceflight-induced-bone Loss Amentioning
confidence: 99%